2006
DOI: 10.1097/00130404-200607000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II Study of Weekly Docetaxel and Vinblastine in the Treatment of Metastatic Hormone-Refractory Prostate Carcinoma

Abstract: This combination of weekly docetaxel and vinblastine is effective, well tolerated, and associated with improved quality of life in most of the patients treated. Although estramustine was not given, the risk of thromboembolic disease remains significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Although this apparently conflicts with the microtubule stabilizing mechanism of docetaxel therapy, in fact there is a variety of evidence supporting our current findings which suggest that the opposite is true. For example, microtubule depolymerizing drugs vinblastine and vinorelbine have shown potent synergy with docetaxel both in vitro and in early clinical trials 36, 37. Additionally, taxane resistance may be mediated by β‐tubulin mutational modification to induce a more unstable microtubular structure,38 which may not tolerate further destabilization by SAMC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although this apparently conflicts with the microtubule stabilizing mechanism of docetaxel therapy, in fact there is a variety of evidence supporting our current findings which suggest that the opposite is true. For example, microtubule depolymerizing drugs vinblastine and vinorelbine have shown potent synergy with docetaxel both in vitro and in early clinical trials 36, 37. Additionally, taxane resistance may be mediated by β‐tubulin mutational modification to induce a more unstable microtubular structure,38 which may not tolerate further destabilization by SAMC treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While phase II trials with various combinations of new drugs have suggested promise for emerging docetaxel combination therapies (Oh et al , 2003; Ferrero et al , 2006; Tester et al , 2006; Kikuno et al , 2007; Garcia et al , 2011), of note is the fact that no drug has yet been shown to provide survival benefit when combined with docetaxel in phase III trials (Antonarakis and Eisenberger, 2013). This suggests that there is a need to identify novel compounds for efficacy as single agents or for use in combination with taxane-based therapies.…”
mentioning
confidence: 99%
“…Third, the purpose of the measure is to accurately record the pain experienced by the dog regardless of the underlying etiology. Like the BPI, the CBPI maintains internal consistency, stability, and positive validity assessments when applied to bone cancer pain from several potential etiologies [23,[33][34][35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%